Religious Program as a Medium for Moral Character Formation in Elementary School: Program Keagamaan sebagai Sarana Pembentukan Akhlakul Karimah di Sekolah Dasar - Mardatillah, Nur Alya; T, Muh. Rusdi; B, Muhammad Rusmin (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Character education in elementary schools plays a vital role in shaping moral and spiritual integrity. Specific background: The Friday Worship Program implemented at UPT SPF SD Inpres Baraya 1, Makassar, integrates religious rituals and moral learning to strengthen students’ spiritual values. Knowledge gap: Limited empirical research explains how structured religious activities foster moral character development among elementary students. Aims: This study examines how the Friday Worship Program contributes to forming students’ akhlaqul karimah (noble character). Results: Using a quantitative ex-post facto design with 155 respondents, data were analyzed through descriptive statistics and linear regression. Findings show that the program reached a moderate implementation rate (70%) and the students’ moral formation reached a similar level (72%). The regression analysis (R = 0.613, R² = 0.376, sig. = 0.000 < 0.05) indicates a significant relationship between the program and moral character formation. Novelty: The study integrates Islamic moral theory (ta’dib) with Bandura’s Social Learning Theory, revealing that attention and motivation are key mechanisms in moral internalization. Implications: Structured religious activities at school can effectively cultivate moral character through teacher modeling and continuous habituation. Highlights Structured religious routines nurture students’ moral consciousness. Teacher modeling and peer interaction strengthen character formation. Religious programs can integrate social learning principles for moral education. Keywords Friday Worship Program, Moral Character, Islamic Education, Social Learning Theory, Elementary School